FORMULASI KEBIJAKAN PENGEMBANGAN SEKOLAH OLAHRAGA DI PROVINSI JAWA TENGAH - Cahyo Bagus Puji Widodo; Slamet Santoso; Aloysius Rengga (Journal of Public Policy and Management Review, 2013)
Education and sports coaching are two things that can not be separated in the lives of student athletes. The condition that eventually led to problems between education and sports coaching student athletes have not been able to run simultaneously, including in Central Java Province. Central Java Province is already running a program named PPLP (Pusat Pembinaan dan Latihan Olahraga Pelajar), but in fact have not been able to overcome the problems of education and sports coaching student athletes. Therefore, it needs a Policy Formulation Development of Sport School in Central Java Province that is expected to be a bridge between education and sports coaching student athletes to be able to overcome the problems of education and sports coaching student athletes in the Central Java Province.